A Short Guide to Operational Risk - Tattam, David (Taylor & Francis, 2025)
There is a growing awareness across both public and private sectors, that the key to embedding an effective risk culture lies in raising the general education and understanding of risk at every level in the organization. This is exactly the purpose of David Tattam's book. A Short Guide to Operational Risk provides you with a basic yet comprehensive overview of the nature of operational risk in organizations. It introduces operational risk as a component of enterprise wide risk management and takes the reader through the processes of identifying, assessing, quantifying and managing operational risk; explaining the practical aspects of how these steps can be applied to an organization using a range of management tools. The book is fully illustrated with graphs, tables and short examples, all designed to make a subject that is often poorly understood, comprehensible and engaging. A Short Guide to Operational Risk is a book to be read and shared at all levels of the organization; it offers a common understanding and language of risk that will provide individual readers with the basis to develop risk management skills, appropriate to their role in the business. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.